Perspectives of cancer consumer representatives on their involvement in healthcare service improvement: a qualitative study - Dan Luo; Jane McGlashan; Klay Lamprell; Gaston Arnolda; Jeffrey Braithwaite; Yvonne Zurynski (BMC, 2024)
Abstract Background Consumer involvement in healthcare service organisation and policy development is recognised globally as a vital strategy in improving the quality and patient-centredness of care. There are significant gaps in knowledge about consumer involvement in practice, including consumers' engagement in the process of enhancing cancer services. This study aimed to explore consumers' perspectives on their involvement in cancer service improvement. Methods Cancer consumer representatives were recruited through Victorian Integrated Cancer Services, Australia. Eligible consumers were, or had been, a member of a health service improvement-related committee or project and attended at least one meeting with health professionals. Semi-structured qualitative interviews were conducted online and transcribed verbatim. Data were analysed using inductive thematic analysis. Results Six experienced consumer representatives were interviewed. Perspectives on their involvement in improving cancer services were categorised into three major topics. The first addressed personal aspects of involvement, in which participants described personal motivations (e.g., having lived experience of cancer themselves or in their family), challenges encountered in committee involvement, experiences of received support in their role as a consumer representative, concerns about narrow representation, and their evolving identity as a consumer representative. The second discussed practical contributions made by consumer representatives to improve systems and services. Participants detailed their active engagement with committees and consumer-led projects, contributing both their cancer experiences and general or professional skills. The third topic focused on directions for improving consumer involvement in the health system. Suggestions highlighted widening consumer representation to include often marginalised voices to inform decision-making at local committee and health system levels. Conclusions This study enhances the real-world understanding of the role that consumer representatives play in improving cancer health services. The strategies suggested in our research provide the opportunity to enhance consumer involvement and pave the way for more effective cancer service planning and implementation across diverse healthcare settings.